(untitled) (International Journal of Environmental Sciences, 2025)
The aim of this research work is to develop optimized colon specific formulation of Budesonide by using design of experiment and evaluate colon specific drug delivery system to treat inflammatory bowel diseases. Budesonide matrix tablets were prepared by wet granulation method using time dependent polymer Eudragit RL100 and coated to prevent initial drug release in gastric region. The formulation was systematically optimized using design of experiment software. Central composite design was employed to study the effect of each independent variable on dependent variables Thickness (mm), Hardness (kg), Drug release (%). (control) and Drug release (%) (test). The Matrix tablets of Budesonide were optimized by using Central composite Experimental Design (2 Factor, 2 Level, and DesignExpert Version 13). The independent variables selected were PVP-30(mg) (X1) MCC PH101 (mg) (X2), and Eudragit RL100 (%) (X3) with their low and high levels for preparing 13 runs of formulations and dependent variable selected were Thickness (mm), Hardness (kg), Drug release (%). (control) and Drug release (%) (test) Finally optimized was selected for further characterization. In vitro drug release study was performed with simulated colonic contents using New Zealand White rabbit. The drug release study in absence of rabbit cecal content medium were carried out using USP II dissolution rate test apparatus (100 rpm, 37±0.5°C) in 900 ml 0.1N HCl for 2 h, Then it is replaced with pH 7.4 phosphate buffer solution, dissolution was continued for 3 h, the dissolution study in pH 6.8 phosphate buffer solution for control was performed without rabbit cecal content. As the usual colonic transit time is 20-30 h, so the dissolution study was continued further for another 24 h. The absorbance was measured using UV/Visible spectrophotometer (UV-730, Jasco) at 246 nm. The graph of cumulative percentage drug release versus time In order to find out best release pattern, the in vitro release drug release data for optimized batches were fitted to Zero order, First order and Higuchi kinetic equations models. As per ICH guidelines, stability study of formulation was performed. TF9’s exceptional friability, combined with its minimal weight variation (0.32%), consistent thickness (0.47±0.03 mm), and precise hardness (4±0.01 kg), underscores its overall superiority in quality and consistency. TF9 is identified as the optimized batch based on its drug content of 99.75±0.01%, hardness measurement of 4±0.01 kg, friability measurement of 0.29%. The kinetic equations were used i.e., Zero, First-order and Higuchi model. Both the kinetic rate constant (k) and the determination coefficient (R2 ) were calculated and presented in graphs. The best fit model with the highest determination coefficient (R2 is 0.9823) value for optimized batch was Zero order.